Diare Pada Balita Perilaku Pencegahan Diare Pada Balita - Kambu, Yunita Kristina; Azinar, Muhammad (Indonesian Journal of Public Health and Nutrition, 2021)
Background: Semarang city area with the most cases of diarrhea in toddlers is in the area of Tlogosari Kulon health center. Puskesmas Tlogosari Kulon with cases of diarrhea in toddlers in 2019, which is as many as 522 cases ranked as the main in the city of Semarang this case decreased from 2018 which is 600. The purpose of this study is to know the description of diarrhea prevention behavior in toddlers in the working area of Puskesmas Tlogosari Kulon. This research was conducted in April-May 2021. Method: This study uses a type of non-experimental quantitative research using a Cross-Sectional design approach method. Informant selected by sampling technique. Results: Statistical test results obtained that the value of p = 0.000 < 0.05, this Ha accepted means that there is a significant relationship of knowledge level with diarrhea prevention. Statistical test results obtained that the value of p =0.012 < 0.05 Ha received means there is a significant relationship between attitude and diarrhea prevention. Conclusion: There is a link between knowledge and diarrhea prevention behavior in Toddlers. There is a link between attitudes and diarrhea prevention behaviors of toddlers. Keywords: knowledge, attitude, behavior of diarrhea prevention ABSTRAK Latar Belakang: Wilayah kota semarang dengan kasus Diare pada balita terbanyak yaitu di wilayah puskesmas Tlogosari Kulon. Puskesmas Tlogosari Kulon dengan kasus diare pada balita di tahun 2019 yaitu sebanyak 522 kasus peringkat utama di kota semarang kasus ini mengalami penurunan dari tahun 2018 yaitu 600. Tujuan penelitian ini mengetahui gambaran perilaku pencegahan diare pada balita di wilayah kerja Puskesmas Tlogosari Kulon. Penelitian ini dilakukan pada bulan April-Mei 2021. Metode: Penelitian ini menggunakan jenis penelitian kuantitatif non eksperimental dengan menggunakan metode pendekatan rancangan Cross-Sectional. Informan dipilih secara Teknik sampling. Hasil: Hasil uji statistik diperoleh bahwa nilai p=0,000 < 0,05, hal ini Ha diterima artinya bahwa ada hubungan yang signifikan tingkat pengetahuan dengan pencegahan diare. Hasil uji statistik diperoleh bahwa nilai p=0,012 < 0,05 Ha diterima artinya ada hubungan yang signifikan antara sikap dengan pencegahan diare. Kesimpulan: Ada hubungan antara pengetahuan dengan perilaku pencegahan diare pada Balita. Ada hubungan antara sikap dengan perilaku pencegahan diare balita Kata kunci: pengetahuan, sikap, perilaku pencegahan diare